THE ANALYSIS OF LEARNING ACTIVITY DURING ONLINE LEARNING IN THE TIME OF COVID-19 - Hakima Maris; Ratih Kusumastuti; Muthmainnah Mursidin; Dada Suhaida (Yayasan Education and Social Center, 2022)
The Covid-19 pandemic has had a considerable impact on the lives of Indonesian people, one of which is in the aspect of education. This pandemic has prompted the government to issue policies regarding the implementation of learning in Indonesia. Namely, learning must carrY out online or remotely. This study describes the implementation of learning activities during online learning in universities. The research method used in this study is a qualitative method with data collection techniques, namely through observation, documentation and interviews. The results of this study illustrate that the implementation of learning activities during online learning in universities has been carried out well. In the implementation of online learning, lecturers have carried out lesson plans. They have carried out learning well, namely using learning media, strategies, methods, and learning approaches tailored to students' needs. Online learning has flexibility in its implementation and can encourage lecturers to be more creative in teaching. Besides that, students must be more independent and motivated to be more active. However, online learning has obstacles in its implementation. Unstable network conditions and difficulties for students to understanding learning materials are challenges in online learning